Dual Interlocking Telescopic Rod Provides Effective Tibial Stabilization in Children With Osteogenesis Imperfecta. Issue 11 (November 2018) - Shin, Chang Ho; Lee, Doo Jae; Yoo, Won Joon; Choi, In Ho; Cho, Tae-Joon
Abstract: Background: Interlocking telescopic rods for the management of osteogenesis imperfecta (OI)-related long bone fractures are a modification of the Sheffield rod. An interlocking pin anchors the obturator at the distal epiphysis, which spares the distal joint, while a T-piece anchors the sleeve at the proximal epiphysis. However, these devices are associated with some problems, including failure to elongate and difficulty with removal. A dual interlocking telescopic rod (D-ITR), in which the sleeve and the obturator are anchored with interlocking pins, was developed to address these problems. Questions/purposes: In this study, we compared the D-ITR with an older version of a single interlocking telescopic rod (S-ITR) based on (1) surgery-free survival and rod survival; (2) cessation of rod elongation and elongated length of the rod; and (3) risk of refracture and complications related to the interlocking telescopic system. Methods: This article compares the D-ITR with the S-ITR using a historically controlled, single-surgeon, retrospective design comparing two implants for the management of fractures in children with OI. Before August 2007, we exclusively used the S-ITR (n = 17 patients, 29 tibiae); from July 2008 until October 2014, we exclusively used the D-ITR (n = 17 patients, 26 tibiae). During the 1-year transition period, we performed five of these procedures (two S-ITR in two patients and three D-ITR in three patients), and implant use was based on availability with our preference being the D-ITR during that time when it was available. The general indications for use of both devices were the same: patients with OI and a tibial fracture who were older than 3 to 4 years of age and whose tibial canals were wide enough to accept an intramedullary rod. Younger patients were treated other ways (generally without surgery) and those with narrower canals with thinner, nonelongating rods or Kirschner wires, as indicated. All patients in both groups were available for followup at a minimum of 2 years (mean ± SD, 9.6 ± 3.0 years in the S-ITR group and 5.3 ± 2.1 years in the D-ITR group) except for one patient in the D-ITR group who died > 1 year after the procedure resulting from reasons unrelated to it. For the between-group comparison, we used only the followup data collected up to the ninth postoperative year in the S-ITR group. The truncated followup period of the S-ITR group was a mean of 5.0 ± 1.6 years. The mean age in the S-ITR group was 7 years (range, 3-12 years) and it was 8 years (range, 3-14 years) in the D-ITR group. There were nine boys and 10 girls in each group. Two orthopaedic surgeons other than the operating surgeon performed chart review to address our three research purposes. Survival analyses were performed using the Kaplan-Meier method. The overall pooled risk of refracture and major complications potentially associated with the interlocking telescopic rod system was compared between the groups. Results: With the numbers available, there were no differences between the D-ITR and the S-ITR in terms of mean surgery-free survival time (5.7 [95% confidence interval CI, 4.5-6.9] versus 5.1 [95% CI, 4.1-6.1]; years; p = 0.653) or mean rod survival time (7.4 [95% CI, 6.4-8.4] versus 6.0 [95% CI, 5.1-6.9] years; p = 0.120). With the numbers available, cessation of elongation (4% in the D-ITR group versus 19% in the S-ITR group; p = 0.112) and elongated length (45.3 ± 24.3 mm in the D-ITR group versus 44.2 ± 22.3 mm in the S-ITR group; p = 0.855) also did not differ between the groups. The pooled proportions of refracture or complications after the index surgery were higher in the S-ITR group (25 tibias [81%]) than in the D-ITR group (15 tibias [54%]; p = 0.049). Eight tibias in the S-ITR group had proximal migration of the sleeve compared with no patients in the D-ITR group (p = 0.005). Conclusions: In patients with OI, the modified D-ITR provides effective tibial stabilization with similar or better results than the S-ITR design. Anchoring the sleeve at the proximal epiphysis with an interlocking pin provides better anchorage and allows easier removal. Level of Evidence: Level III, therapeutic study.